Stem xylem features in three Quercus (Fagaceae) species along a climatic gradient in NE Spain (Trees-Structure and …, 1997)
Stem xylem features in two evergreen Quercus species (Q. coccifera and Q. ilex) and a deciduous one (Q. faginea) were analysed along an Atlantic-Mediterranean climatic gradient in which rainfall and winter cold experi- ence strong variation. Mean maximum vessel diameter, vessel density, vessel element length, xylem transverse sectional area, Huber value (xylem transverse sectional area per leaf area unit), theoretical leaf specific conductiv- ity (estimated hydraulic conductance per leaf area unit) and total leaf area were determined in 3-year-old branches. Q. faginea presented the widest vessels and the highest theo- retical leaf specific conductivity while Q. coccifera showed the lowest total leaf area and the highest Huber value. Studied features did not exhibit significant correlations with mean minimum January temperature in any species but did show significant relationships with rainfall. In Q. coccifera, mean maximum vessel diameter, vessel element length and theoretical leaf specific conductivity increased with higher rainfall while vessel density decreased. Mean maximum vessel diameter and total leaf area in Q. ilex increased with precipitation whereas variables of Q. faginea did not show any significant trend. Results suggest that aridity, rather than minimum winter temperature, controls stem xylem responses in the studied evergreen species. Q. faginea traits did not show any response to precipitation, probably because this species develops deep roots, which in turn makes edaphic and topographic factors more important in the control of soil water availability. In response to aridity Q. coccifera only exhibits adjustment at a xylem level by reducing its water transport capacity through a reduction of vessel diameter without changing the amount of xylem tissue or foliage, whereas Q. ilex adjusts its water transport capacity in parallel to the foliage area.